Modelling the effects of oil prices on global fertilizer prices and volatility - Ping-yu Chen; Chia-lin Chang; Chi-chung Chen; Michael McAleer (Journal of Risk and Financial Management, 2012)
The main purpose of this paper is to evaluate the effect of crude oil price on global fertilizer prices in both the mean and volatility. The endogenous structural breakpoint unit root test, ARDL model, and alternative volatility models, including GARCH, EGARCH, and GJR models, are used to investigate the relationship between crude oil price and six global fertilizer prices. The empirical results from ARDL show that most fertilizer prices are significantly affected by the crude oil price while the volatility of global fertilizer prices and crude oil price from March to December 2008 are higher than in other periods.
Keywords: 330; Risk-return tradeoff; Volatility; Intraday skewness; Quantile Regression; High-frequency data